EMPOWERING RESILIENCE USING BEHAVIORAL ACTIVATION TECHNIQUES - Kushartati, Sri; Sholichah, Mutingatu; Anam, Choirul (Universitas Islam Indonesia, 2023)
The recurrent landslides in the Banjarnegara region has far-reaching consequences, leading to widespread unemployment as agricultural lands become unusable. To enhance the resilience of survivors, an intervention in the psychosocial context was employed, utilizing the behavioral activation technique. Fourteen women, representing family units, spanning ages from 20 to 65, participated in the program. These individuals bore the dual burden of losing their homes and enduring trauma. Analysis of resilience scale data was conducted using the Wilcoxon-signed rank test technique, revealing compelling results with Z=-2.805 and p=0.005 (p<0.01), show a significant increase in the resilience of landslide survivors through the behavioral activation technique. Recommendations for subsequent cycles include: (1) widespread application of the behavioral activation technique to empower other disaster survivors, (2) the implementation of collaborative interventions to address geographic vulnerabilities, and (3) the development of targeted interventions for male survivors to facilitate their return to work in their respective villages.